PENGARUH PROMOTION MIX TERHADAP KEPUTUSAN BERKUNJUNG DI ALAM HEHA OCEAN VIEW YOGYAKARTA (STUDI OCCUPANCY KAMAR GLAMPING) - Evi Yuli Astuti; Uju Suji’ah (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims to determine the effect of advertising, personal selling, sales promotion, publicity, and room sales on visiting decisions, as measured by partial significance test (t test) and simultaneous significance test (F test), the data analysis technique used to answer the hypothesis by multiple linear regression test. The population in this study were all guests of the Glamping room at Alam Heha Ocean View Yogyakarta. The sampling technique used non probability sampling method with a total sample of 138 people. The results of this study indicate that: 1). advertising has a positive effect on the decision to visit, this is evidenced by the significance of 0.047 <0.05, the value of tcount (2.516) > ttable (1.660); individual sales has a positive effect on the decision to visit, this is evidenced by the significance of 0.007 <0.05, tcount (2.760) > ttable (1.660); sales promotion has a positive effect on the decision to visit, this is evidenced by the significance of 0.013 <0.05, the value of tcount (2.438) > ttable (1.660); publicity does not affect the decision to visit, this is evidenced by the significance of 0.594 > 0.05, the value of tcount (0.535) > ttable (1.660); room sales have no effect on the decision to visit, this is evidenced by the significance of 0.550 > 0.05, value (0.599) > ttable (1.660). 2). Advertising, personal selling, sales promotion, publicity, room sales have an influence on the decision to visit, this is evidenced by the significance of 0.042 < 0.05, the value of Fcount (2.965) > Ftable (2.463). 3) Multiple linear equation Y = 16.933 + 0.156 (X1) + 0.313 (X2) + 0.217 (X3) + 0.088 (X4) – 0.123 (X5). 4) The coefficient of determination (R2) is 0.363, indicating that advertising, personal selling, sales promotion, publicity, room sales have an influence on the decision to visit by 36.3%, while 63.7% is influenced by other factors not examined